2021
DOI: 10.1101/2021.04.20.440561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the origins of the European Plagues following the Black Death: a synthesis of genomic, historical and ecological information

Abstract: The Second Plague Pandemic started in Europe with the Black Death in 1346 and lasted until the 19th century. Based on ancient DNA studies, there is a scientific disagreement over whether the bacterium, Yersinia pestis, came into Europe once (Hypothesis 1), or repeatedly over the following four centuries (Hypothesis 2). Here we synthesize the most updated phylogeny together with historical, archeological, evolutionary and ecological information. On the basis of this holistic view, we conclude that Hypothesis 2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Our analyses strongly suggest that local environmental factors in Western and Central Europe, including the chemical composition of the soil, altitude, and climates, did not provide favorable conditions for persistent long-term plague reservoirs maintained by wild rodents and their ectoparasites (11,12,45,46). Indeed, no local European plague outbreaks have arisen over the last century (8,47), while such outbreaks continued to occur across Asia, Africa, and the Americas (48).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our analyses strongly suggest that local environmental factors in Western and Central Europe, including the chemical composition of the soil, altitude, and climates, did not provide favorable conditions for persistent long-term plague reservoirs maintained by wild rodents and their ectoparasites (11,12,45,46). Indeed, no local European plague outbreaks have arisen over the last century (8,47), while such outbreaks continued to occur across Asia, Africa, and the Americas (48).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, there is some phylogenetic evidence suggesting that it may have dwelled in native European wild animal reservoir or reservoirs, capable of maintaining the bacterium for a long period (13,14). On the other hand, and as previously suggested (2,8,11,45,47), human movements may have provided the primary conduits for the reintroduction and persistence of plague in Europe. Human movements may also account for the current Y. pestis phylogeny (11,(51)(52)(53), if we consider that plague was reimported more than once (via commercial routes) from faraway reservoir(s) (11) and spread in Europe by human chains of transmission due to contacts with infected persons or pets, their ectoparasites, or their belongings, as suggested during the Third Plague Pandemic (8,54).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Three main pandemics of plague are recorded in human history: the first plague pandemic spread in Europe and Africa in 541 CE (Little 2007); the second pandemic started in Central Asia in the fourteenth century and rapidly expanded into Europe, where it persisted until the early nineteenth century (Naphy and Spicer, 2004;Bramanti et al 2016;Spyrou et al 2022); and finally, the third pandemic spread from China at the end of the nineteenth century (Bramanti et al 2019(Bramanti et al , 2016Xu et al 2019). Traces of ancient DNA from Y. pestis strains (Bos et al 2011;Bramanti et al 2021;Guellil et al 2020Guellil et al , 2021Haensch et al 2010;Morozova et al 2020;Namouchi et al 2018;Spyrou et al 2019Spyrou et al , 2016Spyrou et al , 2022Susat et al 2020) confirmed the bacterium as the causative agent of the pandemics.…”
Section: Introductionmentioning
confidence: 99%